Analysis of Waste Characteristics at the Mengwitani Recycling Center - I Made Satya Graha; Ni Kadek Intan Yuni Antari; I Made Nada (Jurnal Krisnadana, 2025)
The measurement of waste characteristics (generation, composition, and density) was conducted for 8 consecutive days. The measurement of waste generation refers to the Load-count analysis method by recording the volume and weight of waste as well as the number of waste transport units such as waste carts, trucks, and pickups. The measurement of waste composition and density follows SNI 19-3964-1995, with waste composition consisting of 9 types: food waste, garden waste, plastic waste, paper waste, wood waste, fabric waste, metal wa ste, rubber/leather waste, and others (stones, glass, dust). The results of the study showed the average total waste generation amounting to 28,817 kg and the total waste density amounting to 154.95 kg/m³. The waste composition measurement consists of 9 types: food waste 40.57% with a composition density of 139.17 kg/m³, garden waste 21.19% with a composition density of 130.83 kg/m³, plastic waste 15.95% with a composition density of 85.42 kg/m³, paper waste 5.32% with a composition density of 67.67 kg/m³, wood waste 7.67% with a composition density of 33.33 kg/m³, fabric waste 2.25% with a composition density of 75.34 kg/m³, metal waste 1.10% with a composition density of 40.00 kg/m³, rubber/leather waste 1.08% with a composition density of 202.38 kg/m³, others (stones, glass, dust) 4.87% with a composition density of 166.27 kg/m³. The highest average waste composition is food waste reaching 40.71 kg with an average percentage of food waste reaching 40.57% with a composition density of 139.17 kg/m³. This is because most of it comes from food stalls, restaurants, and markets.